Crossroads [large type] - Franzen, Jonathan (Franzen, Jonathan. Key to all mythologies, 2021)
It's December 23, 1971 and heavy weather is forecast for Chicago. Russ Hildebrandt, the associate pastor of a liberal suburban church, is on the brink of breaking free of a marriage he finds joyless - unless his wife, Marion, who has her own secret life beats him to it. Their eldest child, Clem, is coming home from college on fire with moral absolutism, having taken an action that will shatter his father. Clem's sister, Becky, long the social queen of her high-school class, has sharply veered into the counterculture, while their brilliant younger brother Perry, who's been selling drugs to seventh-graders, has resolved to be a better person. Each of the Hildebrandts seeks a freedom that each of the others threatens to complicate.